Integration of Sustainability Keywords in Digital Marketing for Green Branding - Hesti Respatiningsih; Tri Wahyu Lestari (Politeknik Siber Cerdika Internasional, 2025)
This study investigates how sustainability-oriented keywords can be strategically integrated into digital marketing to strengthen green branding performance among environmentally conscious consumers. The objective of this research is to identify the most effective sustainability keywords, examine their influence on brand perception, and develop a practical framework for optimizing keyword integration across digital marketing channels. Using a mixed-methods approach, the study combines keyword analytics from 1,200 online search queries with qualitative interviews conducted with 15 digital marketing professionals in sustainable business sectors. Findings reveal three dominant keyword clusters—eco-friendly, carbon-neutral, and sustainable materials—that significantly increase search visibility and positively influence perceptions of corporate environmental responsibility. The implications include offering practical guidance for marketers to align keyword strategies with sustainability values, enhancing brand authenticity and competitiveness. The originality of the research lies in presenting an empirically validated green-keyword integration framework that bridges SEO strategy with sustainability communication, a topic understudied in prior digital marketing literature.